Nitrogen uptake and nitrogen fertilizer recovery in old and modern wheat genotypes grown in the presence or absence of interspecific competition - Ruisi, Paolo; Frangipane, Benedetto; Amato, Gaetano; Frenda, Alfonso S.; Plaia, Antonella; Giambalvo, Dario; Saia, Sergio (Frontiers in Plant Science, 2015)
Choosing genotypes with a high capacity for taking up nitrogen (N) from the soil and the ability to efficiently compete with weeds for this nutrient is essential to increasing the sustainability of cropping systems that are less dependent on auxiliary inputs. This research aimed to verify whether differences exist in N uptake and N fertilizer recovery capacity among wheat genotypes and, if so, whether these differences are related to a different competitive ability against weeds of wheat genotypes. To this end, 12 genotypes, varying widely in morphological traits and year of release, were grown in the presence or absence of interspecific competition (using Avena sativa L. as a surrogate weed). Isotopic tracer 15N was used to measure the fertilizer N uptake efficiencies of the wheat genotypes and weed. A field experiment, a split-plot design with four replications, was conducted during two consecutive growing seasons in a typical Mediterranean environment. In the absence of interspecific competition, few differences in either total N uptake (range: 98–112 kg N ha–1) or the 15N fertilizer recovery fraction (range: 30.0–36.7%) were observed among the wheat genotypes. The presence of competition, compared to competitor-free conditions, resulted in reductions in grain yield (49%), total N uptake (29%), and an 15N fertilizer recovery fraction (32%) that were on average markedly higher in modern varieties than in old ones. Both biomass and grain reductions were strongly related to the biomass of the competitor (correlation coefficients > 0.95), which ranged from 135 g m–2 to 573 g m–2. Variations in both grain and biomass yield due to interspecific competition were significantly correlated with percentage of soil cover and leaf area at tillering, plant height at heading, and total N uptake, thus highlighting that the ability to take up N from the soil played a certain role in determining the different competitive abilities against weed of the genotypes.